Threshold of the CAPB that can be attributed to fiscal consolidation episodes in South Africa - Eugene Msizi Buthelezi; Phocenah Nyatanga (Economies, 2023)
This paper investigates the threshold of the cyclical adjusted primary balance (CAPB) that can be attributed to fiscal consolidation in South Africa. The CAPB framework is used in the threshold autoregressive regime (TAR) from 1979 to 2022. The contribution of the paper is the estimation of the CAPB in the context of South Africa to find fiscal consolidation episodes. Moreover, we identify the threshold of CAPB that can be attributed to fiscal consolidation, which the available literature is silent on. The TAR, first-order derivative and dummy variables are employed to find thresholds that can be attributed to fiscal consolidation episodes. By doing so, we provide valuable insights into the underlying dynamics of fiscal consolidation in the country, which can help policymakers develop more effective strategies for managing fiscal consolidation episodes. We estimated the success of fiscal consolidation on government debt in South Africa. There is a threshold of -1.28168%, 1.9182%, and 1.9270% for the CAPB of total government revenue increase, government expenditure cut, and the CAPB as a sum of both revenue and expenditure, respectively. These thresholds are different from the threshold of 1.5% advocated in the literature. It is recommended that a country-based threshold be used to find fiscal consolidation episodes. No or less fiscal consolidation is needed, as it results in less chance of reduction in government debt. Fiscal authorities must establish and execute a strategy for managing domestic government debt to avoid increasing its risk.
Keywords: E62; H50; 330; fiscal consolidation episodes; cyclically adjusted primary balance (CAPB); threshold autoregressive regime (TAR)